Buddhist Philosophy in Thai Education: Integration of Mindfulness Practices in Primary School Curriculum - Siriporn Rattanapinyowong (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2024)
This study examines the integration of Buddhist philosophy and mindfulness practices in the primary school curriculum in Thailand, a nation where Buddhism profoundly shapes the cultural and educational landscape. The purpose of this research is to explore how the "Buddhist-Oriented Schools" program is implemented, and to understand stakeholder perceptions and the impact of these practices on students. Using a qualitative case study design in two primary schools in Chiang Mai, data were collected through participant observation, semi-structured interviews, and document analysis. The findings indicate that mindfulness practices, such as short meditations and mindful pauses, have been successfully integrated into classroom routines to improve student focus and emotional regulation. This implementation is explicitly based on Buddhist philosophy (Trisikkha) but is delivered in accessible, universal language. The success of the program is highly dependent on the teacher's role as the primary facilitator, although challenges such as a lack of advanced training and resources remain obstacles. In conclusion, this Thai educational model offers a valuable example of an authentic cultural adaptation of mindfulness practices, effectively enhancing student well-being while remaining rooted in local wisdom.